Application of Chlorella pyrenoidosa embedded biochar beads for water treatment. (April 2021) - Guo, Qicong; Bandala, Erick R.; Goonetilleke, Ashantha; Hong, Nian; Li, Yuqing; Liu, An
Graphical abstract: Highlights: Biochar beads embedded with freshwater algae was prepared for water treatment. Freshwater algae within the beads primarily removed nutrients by assimilation. Biochar mainly removed organic matter and heavy metals by chemisorption. Beads have potential to be used in estuarine/marine areas and saline groundwater. Feasibility of combining freshwater algae and biochar to treat water was confirmed. Abstract: The ability of biochar beads embedded with freshwater algae ̶ Chlorella pyrenoidosa (Bc-Cp beads) were investigated for their efficiency in the removal of pollutants. Combining these is an innovative concept which can result in improvements in pollutant removal since both, biochar and algae have the ability for adsorbing/absorbing pollutants. Additionally, only limited work on embedding freshwater algae (common algae existing in surface water and having low ecological risks since they are native species) into biochar for the removal of water pollutants has been undertaken to-date. It was found that Bc-Cp beads prepared using 10 mL of algae (9 × 10 8 cell/mL), 0.3 g of biochar, 40 g/L of sodium alginate, and 20 g/L of CaCl2 displayed the optimum characteristics including mechanical strength (2.548 N), promotion of algae growth (191.70 % growth rate) and pollutant removal ability with the removal efficiency of ammonia nitrogen, total nitrogen and total phosphorus, total organic carbon, zinc and copper were up to 69.2 %, 43.0 %, 73.8 %, 81.0 %, 74.4 % and 81.0 %, respectively. The algae within the beads were primarily responsible for the removal of nutrients by assimilation, while biochar mainly exerted influence on the removal of organic matter and heavy metals by chemisorption. The study outcomes also confirmed that Bc-Cp beads possess high potential to be used in estuarine environments and saline groundwater.